Trade, Superstars, and Welfare - Bohdan Kukharskyy (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2012)
In recent decades, many countries experienced both a rise in top income shares and an increase of income inequality among the top earners. In this paper, I study the role of international trade as a catalyst for this development and analyze the associated welfare effects. I build a simple general equilibrium model that incorporates Lucas' (1978) idea of individual heterogeneity regarding managerial talents into the framework of intra-industry trade with two symmetric countries. By scrutinizing effects of trade integration on entrepreneurial compensation and endogenous occupational decisions, this model can reproduce the observed pattern of income changes in the top percentiles. Despite positive joint welfare effects of trade liberalization, individual gains from trade may be non-monotonic in agents' skills. While the welfare of workers and most productive entrepreneurs unambiguously rises, the least- and medium-productive entrepreneurs may be worse off, if their preferences for the traded goods are small enough.
Keywords: F12; F16; J24; D31; 330; Distributional effects of trade; individual welfare; occupational choice; superstars.; Managervergütung; Einkommensverteilung; Führungskräfte; Außenwirtschaft; Globalisierung; Außenhandelsgewinn; Wohlfahrtsanalyse; Theorie